Development of a Web-Based Online Library Information System at the National University Using the Waterfall Method: Development of a Web-Based Online Library Information System at the National University Using the Waterfall Method - Heru Saputro; Iwan Wahyudin; Agus Iskandar (Institute of Computer Science (IOCS), 2020)
The definitions of Pustaka places or libraries are: Several source charts from schools to lectures have not escaped the info-info/knowledge from the library. In relation to the advancement of this technology makes: people to be able to mind effectively also efficient work. For example: conventional systematic generation is more computerized.From the utilization of a feature of the web connected online, the de also: increased levels of efficiency and effectiveness in the book Search and booking. This research designed a website based information system with PHP. From the results of research that has been implemented authors implement the results of the research on: Development of information Systems Web based Online Library of national universities using Waterfall method